The PainSMART project: Protocol for a research program on effectiveness, mechanisms of effect and patient-practitioner experiences of the PainSMART-strategy as an adjunct to usual primary care physiotherapy management for musculoskeletal pain - Richard Thompson; Maria Fors; Ann-Sofi Kammerlind; Pia Tingström; Allan Abbott; Kajsa Johansson (PLoS ONE, 2025)
Background Musculoskeletal pain (MSKP) disorders entail a significant burden for individuals and healthcare systems. The PainSMART-strategy has been developed aiming to reduce divergences between patients and healthcare practitioners in their understanding of MSKP by providing a shared basis for communication and to facilitate patients’ self-management of MSKP. The objective of the PainSMART-project is to evaluate the effects of the PainSMART-strategy as an adjunct to usual physiotherapy management compared to usual physiotherapy management alone. Methods The PainSMART-project is a research program with a collective suite of studies utilising mixed methods, centred around a randomised controlled trial (ClinicalTrials.gov NCT06187428). Subjects: Adults (18 years or older) seeking primary care for MSKP who are triaged and booked for an initial physiotherapy consultation at five primary care physiotherapy departments within the Swedish public healthcare regions of Östergötland and Jönköping. A total of 490 subjects will be randomised to receive one of two possible interventions. Interventions Both groups will receive usual physiotherapy management for benign MSKP. The intervention group will also receive the PainSMART-strategy consisting of an educational film, reflection and reinforcement of the film’s key messages prior to the initial physiotherapy consultation and a patient-practitioner discussion based on the film. Outcome The primary outcome is 1) between group mean change over time from baseline to 24 hours post initial physiotherapy consultation and baseline to 3 months regarding self-reported average pain intensity and pain self-efficacy. Secondary outcomes include similar measurements for MSKP illness perception, reassurance of benign nature, pain coping, physical activity, analgesic medication use, sick leave, healthcare use and direct healthcare costs. Physiotherapist and patient reported experience measures and qualitative evaluation of the effects of the PainSMART-strategy on communication at the initial physiotherapy consultation will also be explored. Discussion This study will investigate potential added effects of PainSMART-strategy upon usual primary care physiotherapy for MSKP.